Depiction of Viable Tumor in Hepatocellular Carcinoma Treated with Transarterial Chemoembolization: Multiphasic Helical CT with Review of the Previous Serial CT Images - Jang, Kyung Mi (The Korean Radiological Society, 2005)
OBJECTIVE: The purpose of our study was to assess whether a review of multiphasic helical CT combined with the previous serial CT images could be helpful to depict a viable tumor in hepatocellular carcinoma treated with transarterial chemoembolization. MATERIALS AND METHODS: Twenty-four consecutive patients with 35 hepatocellular carcinomas underwent transarterial chemoembolization followed by hepatic resection. First, three radiologists independently analyzed the last CT images taken before resection for the presence of viable tumor. A second analysis was then performed using the last CT combined with the previous serial CT images. The CT analyses were then compared with the pathologic results. The added value of the review of the previous serial CT images was evaluated by performing a receiver operating characteristic analysis. The sensitivity, specificity and diagnostic accuracy for the depiction of viable tumor were also assessed, and the characteristics of the false-negative lesions were pathologically evaluated. RESULTS: The mean diagnostic accuracies (Az values) for the depiction of viable tumor with using the last CT alone and with the review of the previous serial CT images for all observers were 0.885 and 0.901, respectively, which were not significantly difference (p > 0.05). However, the additional review of the previous serial CT images allowed the observers to render a correct diagnosis for three lesions that had been incorrectly diagnosed with the review of last CT alone. The sensitivity, specificity and diagnostic accuracy of the last CT along with the review of the previous serial CT images were 78%, 97% and 84%, respectively. All of the 16 false-negative lesions diagnosed by each observer showed 90% or greater necrosis on the pathologic examination. CONCLUSION: For the depiction of viable tumor in hepatocellular carcinoma treated with transarterial chemoembolization, although the difference in the diagnostic accuracies was not statistically significant, a review of the multiphasic helical CT combined with the previous serial CT images could help reach a correct diagnosis for those lesions incorrectly diagnosed with the review of the last CT alone.